Severe Xanthogranulomatous Pyelonephritis With Staghorn Calculi and Perinephric Abscess: A Case Report - Manar Ashour MD; Ahmed Dheyaa Al-Obaidi MBChB; Shahzaib Ahmed MBBS; Nizar Alyassin MD; Mustafa Almusawi MD; Hashim Talib Hashim MBChB (Journal of Investigative Medicine High Impact Case Reports)
Xanthogranulomatous pyelonephritis (XGP) is a rare, severe form of chronic kidney infection that mimics renal malignancies, often leading to diagnostic challenges. We present the case of a 36-year-old woman with a 2-month history of progressive lower back pain, fever, and weight loss. Imaging revealed left renal enlargement with multiple low-attenuation areas and large staghorn calculi, suggestive of XGP. Middle-aged women are primarily affected by recurrent urinary tract infections and renal calculi, leading to extensive renal destruction. Characteristic “bear paw” sign on computed tomography suggests XGP; however, histopathological confirmation is required. Early recognition and intervention are essential to prevent irreversible renal damage. Our case highlights the need for clinical awareness and prompt evaluation to minimize disease burden and improve patient outcomes.